Pengaruh Kualitas Layanan Terhadap Kepuasan Pengunjung Rumah Tahanan Negara (Rutan) Kelas IIB Gresik - Putra, Nurendo Imam; Lestari, Damajanti Sri; Liling Listyawati (Journal Of Accounting and Business, 2024)
This research aims to determine the influence of service quality on visitor satisfaction at the Class IIB Gresik State Detention Center, both simultaneously and partially and to determine the percentage influence of 5 variables, Reliability, Responsiveness, Assurance. , Empathy (Empathy), Tangibles (Physical Evidence) on visitor satisfaction at the Class IIB Gresik State Detention Center (Rutan). This research is quantitative research with a causal approach. The population in this study were all visitors to the Class IIB Gresik State Detention Center who visited within a period of 1 month, namely in January 2024. The number of samples determined was 100 respondents who had been distributed via a questionnaire via Google form which was distributed by the researcher to the visitors at the time. visitors visit the Class IIB Gresik Detention Center. This research uses a simple random sampling technique to collect respondents and uses the Unknown formula to determine the sample because the population size in this study is unknown. Next, the data was analyzed using instrument tests, classical assumption tests, multiple linear regression tests, F tests, t tests, and simultaneous and partial coefficient of determination tests. The results of the research show that the 5 variables Reliability, Responsiveness, Assurance, Empathy, Tangibles have an influence of 76.1%, both simultaneously and partially, on the satisfaction of home visitors. State Prisoner (Rutan) Class IIB Gresik. and 23.9% was influenced by variables not examined in this study.